If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 17 + -4x = -8 + -11 Reorder the terms: 17 + 5x + -4x = -8 + -11 Combine like terms: 5x + -4x = 1x 17 + 1x = -8 + -11 Combine like terms: -8 + -11 = -19 17 + 1x = -19 Solving 17 + 1x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 1x = -19 + -17 Combine like terms: 17 + -17 = 0 0 + 1x = -19 + -17 1x = -19 + -17 Combine like terms: -19 + -17 = -36 1x = -36 Divide each side by '1'. x = -36 Simplifying x = -36
| x^2+4x=-40 | | (2(y-3))/3=-3y | | (4x+16)/(8)=2x-1 | | -3-11=9x+15-8x | | (4(y-5))/3=-4y | | -x-7y=-18 | | 2-5i=-x+10yi | | -9x+5+10x=-11+13 | | n-12=24 | | (7/2)+(5/2y)=2y-3 | | y=3(3)-9 | | 176-4x=23x+17 | | 0.17-0.01(x+2)=0.03(3-x) | | 9(x+1)-1=3x+6(1+x) | | 5c-7c=(-32) | | 8+3x=24+14 | | 18a-45b-9c= | | A-x=3a | | (x/4)-1=(x/9)+4 | | 4(x-5)=2x+25 | | 4x-3(3x-9)=12 | | y/4+y=10 | | g+10/3=10 | | 5c(3c+2d)-2c(c-d)= | | y^2+5y+6y^0=0 | | ((4x+5)(6)(2x+5)^2+(-8)(2x+5)^3)/(4x+5)^3 | | 81t=-8.1 | | 4p+28q+12r= | | 175 x 104 = | | -7x+9=7x-47 | | 3/7+k/8=5/56 | | 0.36=18 |